Encryption and hiding text using DNA coding and hyperchaotic system - Zeena N. Al-Khateeb; Melad Jader (Institute of Advanced Engineering and Science, 2020)
In this paper, a secure data encryption using DNA sequence operation in a new and innovative direction different from the traditional direction, DNA coding uses the eight rules of DNA code based on a sequence of letter in text that provides the possibility of encrypting the same letter or word in more than one form in one text-based on sequence of this letter or word in the text. Then hiding technique implemented based on a hyperchaotic system. To increase the security of encryption text, we use the hyperchaotic system for obtaining the color image position that used to hide on it. The proposed steganography method hides a letter of the encrypted text in each pixel of the cover image, thus giving the possibility of hiding large text data. Some metrics have been applied to the proposed algorithm such as NPCR analyses, MSE, Correlation, and BER, The results of the simulation and security analysis showed that the new DNA coding is suitable for text encryption/decryption and that the super-chaotic map is suitable for hiding/extract the encrypted data, which indicates that the proposed encryption algorithm has a good encryption and hiding effect. Can resist brute statistical attack, force attack, differential.